Effects of different manual periodontal probes on periodontal measurements - Holtfreter, Birte (2012)
AIM: To quantify the digit preference effect for three manual periodontal probes and to calculate correction values to enable comparison of studies with equal recording protocols, but different periodontal probes. MATERIAL AND METHODS: A prospective in vivo crossover study was conducted with a six-sequence three-period design. Six examiners assessed attachment loss (AL), probing pocket depth (PD) and gingiva height (GH) at four surfaces, full-mouth, in six generally healthy subjects using three manual probes: PCP11 (3-3-3-2 mm increments), PCP2 (2 mm increments), and PCPUNC15 (1 mm increments). RESULTS: Distributions of AL, PD and GH differed between probes (p < 0.001). Compared with PCPUNC15, periodontal measurements coinciding with probe markings of PCP11 and PCP2, respectively, were preferentially named by examiners. Digit preference was most pronounced for PD, but less for AL and GH. In multilevel models, PD differed significantly between all three probes (p < 0.05); probe- and examiner-related effects were also observed for AL and GH. Correction values for pairwise combinations of probes were determined. CONCLUSIONS: We provided empirical evidence and quantified the effect of probe type on periodontal measurements. Differences in probe type should be considered when comparing periodontal data within and between epidemiological studies and appropriate corrections, provided here, should be applied.